Planar Positive–Zero–Negative Thermal Expansion Transition in Crystalline Supramolecular Rotors - Ge, Si-Yuan; Huang, Rui-Kang; Wu, Jia-bing; Takahashi, Kiyonori; Lee, Chi-Sing; Nakamura, Takayoshi (Chemistry of materials, 2023)
Zero thermal expansion materials are crucial for manufacturing high-precision devices, but most of these materials discovered so far are inorganic. Organic zero thermal expansion materials are rare due to the need for precise control over the complex supramolecular interactions between organic groups in order to modulate their thermal expansion properties. Here, we report a novel organic crystalline supramolecular rotor, [(3-chloro-1-adamantylammonium)(18-crown-6)]ClO4, which exhibits planar positive–zero–negative thermal expansion along the a- and c-axes, with zero thermal expansion behavior in the range of 250–317 K. X-ray single-crystal structures, differential scanning calorimetry (DSC) measurements, and molecular dynamics simulations disclosed that such unique transition in thermal expansion results from the static–swing–rotation transition of 18-crown-6 in the crystal structure.